(untitled) (Scientific journal of the Fergana State University, 2023)
In the article the issues of historical-cultural values in the moral heritage are analyzed. Human education in the historical-spiritual values and the importance of it’s in maturity. The article also about spiritual exaltation of society and person which plays an important role in development of thinking and the formation of values is reported.